Estradiol and genistein effects on the sea bass (Dicentrarchus labrax) scales: transcriptome dataset - Pinto, Patricia IS (2019)
Fish scales are mineralized structures that play important roles in protection and mineral homeostasis. This tissue expresses multiple estrogen receptor subtypes and can be targeted by estrogens or estrogenic endocrine-disrupting compounds, but their effects are poorly explored. The transcriptome data here presented support the findings reported in the research article "Genistein and estradiol have common and specific impacts on the sea bass (Dicentrarchus labrax) skin-scale barrier" [1]. Juvenile sea bass were exposed to estradiol and the phytoestrogen genistein for 1 and 5 days, by intraperitoneal injections, and the effects on scale transcript expression were analysed by RNA-seq using an Illumina Hi-seq 1500. The raw reads of the 30 libraries produced have been deposited in the NCBI-SRA database with the project accession number SRP102504. Mapping of RNA-seq reads against the sea bass reference genome using the Cufflinks/TopHat package identified 371 genes that had significant (FDR<0.05) differential expression with the estradiol or genistein treatments in relation to the control scales at each exposure time, 254 of which presented more than a 2-fold change in expression. The identity of the differentially expressed genes was obtained using both automatic and manual annotations against multiple public sequence databases and they were grouped according to their patterns of expression using hierarchical clustering and heat-maps. The biological processes and KEGG pathways most significantly affected by the estradiol and/or genistein treatments were identified using Cytoscape/ClueGO enrichment analyses.